The Suomen antropologi Ethnographic Reading Challenge - Henni Alava; Tuomas Tammisto (Suomen Antropologi, 2024)
Each year just before the New Year, our hometown library—the Helsinki Metropolitan Area Library Network (Helmet 2024)—issues a curated 50-book reading challenge. To celebrate a new year, Suomen antropologi: Journal of the Finnish Anthropological Society, presents an ethnographic reading challenge in a similar style. The challenge is an outcome of one recent Friday evening when we—middle-aged neighbours and colleagues who did not know what else to do with our free time—went for a walk to our local library. Woven into this reading challenge is a bid for something more. The categories in this challenge purposely extend across broad, or ambiguous, categories, at times bordering on the downright silly. Our intention is to encourage thoughtful reading of ethnographies and other books that inspire our ethnographic imaginations.